Child-centered Education in Indian Schools: Policies and the Practice - Paltasingh, Dr. Tattwamasi; Bhue, Prakash (Voices of Teachers and Teacher Educators, 2021)
Child-centered education has been a long-held dream for Indian schools. It has occupied an important place in formal schooling since the National Policy on Education -1986 was introduced. During the last few decades, several initiatives have been taken through the curriculum framework, teachers’ training, and various plans and policies to make the teaching-learning process child-centered. But a large number of schools in India are yet to practice child-centered education. The National Education Policy-2020 has set a target of five years to develop the foundational learning and numeracy of the children by restructuring the pedagogy and teacher education. This paper is an attempt to highlight the barriers to implementing with child-centered education in Indian schools and suggest an effective pedagogical approach for inclusive school education.